HUMETAV model for citizen science initiatives: designing socio-ecological projects to foster awareness - Sanabria-Z, Jorge; Santana-Castellón, Eduardo; Olivo, Pamela; Molina-Espinosa, José Martín; Artemova, Inna; Irwin, Terry; Kossoff, Gideon; Sánchez-Ruano, David; Succini, Laura; Velarde-Camaqui, Davis; Platero-Fernández, Néstor Gabriel; Quintero, Lorena; et al. (Frontiers in Education, 2025)
The socio-ecological impacts of climate change, biodiversity loss, and globalisation are becoming increasingly evident locally and globally. While efforts are being made to sensitise citizens through environmental and ecological education, the impetus for their active participation in addressing growing socio-ecological problems is still lagging behind. In this context, this study presents the design and testing process of a citizen science workshop based on the HUMETAV model, as applied in the Museum of Environmental Sciences of the University of Guadalajara. This is an initiative driven by Transition Design to raise awareness among youth about the socio-ecological importance of connecting nature and the city through techno-creative empowerment. We begin by presenting the visual representation of the HUMETAV model, which is crucial to understanding the scope of this development. This paper has followed the Design Process and Design Practice design methodology to define the HUMETAV–Citizen Science workshop to test the HUMETAV model. The findings of this study are that (a) the HUMETAV model can be applied to citizen science as a pedagogical tool; (b) the Design Process and Practice methodology is suitable for the development of educational training activities; (c) the Transition Design and Threshold for Citizen Science Projects framework effectively guides the design of citizen science proposals; (d) feedback engagement transforms participants into vital co-creators, mirroring citizen science practices; and (e) a student-teacher-mentor inter-group structure is a catalyst for long-term online workshop success by emphasising the importance of collaboration. The implications of this study for educational communities lie in the benefits of applying a model that empowers youth through a co-designed, interdisciplinary approach in real-world environments to improve socio-ecological conditions. Future research can build on these findings to explore the applicability of the HUMETAV model across diverse educational settings.